2012
DOI: 10.1097/htr.0b013e3182168fb1
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Factors Associated With Perceived Success in the Transition From Hospital to Home After Brain Injury

Abstract: : A combination of sentinel events and personal and environmental factors influences the perceptions of individuals and their families regarding the success of the transition from hospital to home.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
50
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(50 citation statements)
references
References 38 publications
(43 reference statements)
0
50
0
Order By: Relevance
“…It is widely acknowledged that adults with acquired brain or spinal injury or progressive neurological illness (e.g., Multiple Sclerosis; Cerebral Palsy) incur significant housing challenges post diagnosis (Cameron, Pirozzo, and Tooth 2001;Foster, Fleming, and Tilse 2007;Nalder et al 2012). Due to the complex physical and/or cognitive nature of their condition, individuals living with a neurological disability often require assistance with activities of daily living (ADL) and personal care.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is widely acknowledged that adults with acquired brain or spinal injury or progressive neurological illness (e.g., Multiple Sclerosis; Cerebral Palsy) incur significant housing challenges post diagnosis (Cameron, Pirozzo, and Tooth 2001;Foster, Fleming, and Tilse 2007;Nalder et al 2012). Due to the complex physical and/or cognitive nature of their condition, individuals living with a neurological disability often require assistance with activities of daily living (ADL) and personal care.…”
Section: Introductionmentioning
confidence: 99%
“…The housing challenges experienced are reflective of a broader and persistent issue relating to housing availability as well as the problem with housing suitability. In the case of acquired neurological injury, once the person is deemed medically stable by a physician or able to function semiindependently, arrangements are made to refer the person back to: (a) their family home, where the infrastructure often requires modifications; or (b) some form of supported accommodation or residential care facility (in instances where the family home is not an option) to continue their care and support as needed during this initial recovery period (Beer and Faulkner 2008;Cameron, Pirozzo, and Tooth 2001;Foster, Fleming, and Tilse 2007;Nalder et al 2012).…”
Section: Introductionmentioning
confidence: 99%
“…How caregivers cope can adversely affect the status of their health (1,11,14,18).As for their health problems, emotional functioning, mental and physical health, many studies (29)(30)(31)(32) clearly note correlations with the recovery outcomes of survivors with TBI in the rehabilitation phase. However, the caregivers in this study reported more problems with physical health than emotional functioning and mental health.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, it is imperative that community ambulation is addressed during inpatient rehabilitation. This will allow for increased confidence with exploring community environments and tasks (Walsh et al, 2014) and reduce the incidence of sentinel events, which can lead to avoidance of communitybased activities (Ahuja et al, 2013;Barnsley et al, 2012;Nalder et al, 2012a;Nalder et al, 2012b) and poor community re-integration. Another option is the implementation of communitybased rehabilitation or community follow-up for all stroke survivors following hospital discharge.…”
Section: The Effect Of Current Practices On Free-living Ambulation Rementioning
confidence: 99%
“…During the subacute phase of stroke, stroke survivors display the greatest potential for improvement in functional outcomes (Jang, 2010;Carod-Artal et al, 2000;Jorgensen et al, 1995b). Further, experiences such as sentinel events, or mismatched expectations of recovery that can occur early after stroke survivors return home from hospital can change expectations of outcome and engagement in walking related activities if not sufficiently supported (Ahuja et al, 2013;Barnsley et al, 2012;Nalder et al, 2012a;Nalder et al, 2012b). Thus, this immediate phase post hospital discharge is important to target during recovery to ensure optimal outcomes later after stroke.…”
Section: Introductionmentioning
confidence: 99%